Correlation of Sex & BMI with Fusion of Human Sternum in ‘Bengalee’ Population from Dead Bodies Sent for Autopsy in NRSMCH Morgue - Sayak Sovan Dutta; Sandip Mukhopadhyay; Subhajit Adhikary (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Sternum is the bone which gives a fair idea for the estimation of age in the later decadesof life. It is a well established fact that factors like endocrinal, heredity, climate, diatic habits have certaindegree of influence over bony union and it is also proved that epiphyseal union occurs one to two yearsearlier in females than in males. BMI (Body Mass Index) is defined as person’s weight in kilograms dividedby the square of height in meters. Methods: The aim of the study is to establish any Correlation of sex andBMI with the fusion of different parts of Sternum in Bengalees.120 sternums are studied in this study overa period of 1.5 years from the dead bodies of ‘Bengalee’ persons sent for Post Mortem examination in theHospital morgue, Department of Forensic Medicine & Toxicology, N.R.S Medical College & Hospital,Kolkata. Concussion: There was no significant difference between male and female in respect to the agesshowing fusion. When the BMI of the subjects were compared with different grades of fusion between thesternal segments, significant statistical correlation was found between the fusion of sternebrae and the BMI,but fusion of Xiphisternum and Manubrium with Mesosternum did not show any statistically significantcorrelation. Sexual variation of ages for fusion of sternum was not found in ‘Bengalee’ population. Nutritionalstatus has a significant effect on the fusion of the sternebrae with each other, but no significant effect on thefusion of xiphisternum and manubrium with body of sternum.